Malaysia’s public policies to foster inclusive and accountable governance - Quddus, S. M. Abdul (2016)
Malaysia’s public policies such as the New Economic Policy (NEP) and recently introduced 1Malaysia ‘concept’ are widely viewed by other developing societies as ‘success stories’ of inclusive development. In fact, affirmative action under the NEP were undertaken as a consequences of the 1969 ‘crisis’ to address gross socioeconomic inequalities of ethnic groups that has emerged during British colonial era. Forced migratory and settlement patterns introduced by the colonial government in 13 states in Malaysia created a sense of powerlessness among marginalized groups. The 1969 ‘crisis’ was the outcome of postcolonial development policies that had done little to redress wealth and income disparities of these marginalized groups and in particular ethnic Malays. Therefore, the NEP was introduced in 1970 involving extensive state intervention in the economy with the aims to eliminate poverty and alleviate wealth and income inequalities between ethnically-defined communities. The results of such well-managed public policies to resolve socioeconomic injustices and distribution of wellbeing in the society were impressive. For example, the NEP helped to reduce poverty to 3.8 per cent in 2009 compared to 64.8 per cent in 1970 (Gomez & Saravanamuttu, 2013:2&9). The official corporate ownership figure of the targeted community i.e. the Bumiputeras and government trust agencies increased to 21.9 per cent in 2009 from a mere 1.5 per cent in 1969 (Tenth Malaysia Plan, 2011-2015; p. 403). Public policies under the NEP facilitated the opportunities for the Bumiputeras to have access to quality public higher education and study in abroad with government scholarships, government employment, private sector employment and equity ownership, etc. The NEP and the Rukunnegara (National principles) stressed for national unity and the creation of a just and liberal society by correcting of ethnic imbalances in the areas of income, employment and ownership of capital. This paper deals with the following research questions: (a) what were the socioeconomic conditions in Malaysia before the 1969 ‘crisis’? (b) why postcolonial regimes felt encourage to adopt public policies based on affirmative action such as the NEP to address gross socioeconomic inequalities of ethnic groups? (c) what are the consequences of policy goals of the NEP and how to overcome the problems (if any)? The concept of “horizontal” public policies suggested by Stewart et al. (2008) has been used as a theoretical guideline in this paper. It deals with inclusive development of culturally defined groups such as ethnic, religious, racial or caste-base groups. Data from published secondary sources such as government policy papers, consultancy and media reports, etc will be consulted. This paper argues that policy initiatives under the NEP have had positive impacts on resolving socioeconomic injustices and distribution of wellbeing of the majority group in the society i.e. ethnic Malays. However, these policies have also created problem of interethnic social cohesion, inhibited genuine entrepreneurial capacity and contributed to serious new intra-Bumiputera inequities in addition to brain drain due to frustration, reluctance by some domestic enterprises to invest in the economy and a decline in the quality of public institutions and services (Hill et al. 2011: Mukherjee and Wong, 2011). Considering the further marginalization of other ethnic groups such as Orang Asli, Chinese and Indian communities in the country, Najib Razak has recently introduced a new concept 1Malaysia, involving a call for greater ‘inclusion’ of the needs of all Malaysian in public policies. Although there are services for all communities in Malaysia under 1Malaysia programs but many observers pointed out that these activities are superficial and the direction of 1Malaysia concept is unclear.